Contact tracing: a global perspective and recommendations for the Indian scenario - Puntambekar, Varad; Sharma, Parth; Mulchandani, Manish (International Journal Of Community Medicine And Public Health, 2020)
We are currently in the midst of a pandemic of SARS-COVID-19 that has spread and increased its reach geometrically in just 3 months. Different countries and states are employing multiple methods to decrease the spread of the virus and decrease its negative impact. The government of India also has taken steps to identify and trace all patients and their contacts. This requires immense input of manpower, finance and technological solutions. Models from India and all over the world act as guides in highlighting the advantages and pitfalls of this method. Models of South Korea, Taiwan and Singapore, where intensive contact tracing measures have been implemented have been successful in controlling the pandemic but have created issues of invasion of privacy. Most successful models, in the developing world have sought out to create a multi-disciplinary dedicated contact tracing team of roughly 2-3 contact tracers per 1000 population. It is important to set up a dedicated team for this so that the already stretched ASHA and other community health workers are not overburdened as more responsibilities might lead do decrease in quality. Such a team, which is sensitive to local customs and armed with basics of contact-tracing techniques, need not be highly educated. Technological solutions that keep user privacy as a priority and encourage transparent sharing of methodologies to ensure user privacy must be promoted. Solutions must ensure dissemination of information from trusted sources and self-monitoring of symptoms.